Organizational Restructuring and Change in Transition Societies: Dominant Coalitions and the Dynamics of Managerial Power and Politics. (May 2013) - Soulsby, Anna; Clark, Ed
The authors argue that a fuller understanding of processes of organizational restructuring in transforming societies emerges from studying not only the expressed motives behind senior managers' actions but also how these political actions are located within the emergent structural context of power, domination and legitimacy. The politics of restructuring in two former state-owned enterprises and the different strategies top management teams adopted to sustain a favourable internal and external balance of power and control the processes of legitimation, order and opposition are examined. The authors argue that the experiences of the enterprises illustrate two distinct patterns of relationship between forms of managerial politics and processes of enterprise restructuring within transitional circumstances.